Showtime! - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha, 2018)
"The King and Queen have put Sasha in charge of planning a Summer Solstice celebration for the horses of Verdant Valley and Crystal Cove! Sasha has never planned a big party before, and there are so many details! Will she find a way to pull this party off?"--